Environmental Engineering Graduate Study Program - UTAMIPUTERI (NIM: 25313043), ISWIATI
Coastal aquaculture activity is one of the activities that support thecoastal communitiesÃ‚Â’ economy. The rapid development of aquaculture areas may result in water quality degradation. It is caused by the effluent from ponds containing high nitrogen that can also disrupt aquatic ecosystems. On the other hand, sea water is also used as inputs in water aquaculture activities. Research in predicting the distribution of nitrogen, devoted around the ponds in the coastal waters of Karawang. The purpose of this study is to determine the nitrates distribution from ponds waste in coastal waters, both spatially and temporally which influenced by the condition of ups and downs as well as ocean currents. Prediction is done using MIKE 21 software that can predict the hydrodynamic conditions and model the transport of waste. Based on current circulation predictions, it is obtained that during spring tide at the highest tide and lowest tide, the current flows from the northwest to the southeast and southest to the northwest, respectively. The prediction of nitrate distribution shows that nitrate spread towards the furthest offshore with a concentration of 1 mg/l occur at low tide during spring tide along 1,7 km distance to the northeast. At high tide during neap tide, a concentration of 1 mg/l of nitrate moving along 1.3 km from the coastline towards the offshore. The condition of the nitrates distribution on the coastal waters around Pandu Karawang Ponds proven highly influenced by the tidal conditions and follow the dominant direction of the currents in the area.